Acoustical characterization of nickel aluminide (Ni3Al) at low temperatures. Issue 1 (March 2021) - Pandey, Krishna Kumar; Lahariya, Vikas; Tiwari, Balgovind; Mathuriya, Abhilasha Singh
Abstract: Present research work deals with the acoustical characterization of Nickel Aluminide (Ni3 Al) at low temperature region from 10K to 50K. Particularly, the Ultrasonic waves have been used as a Non-destructive testing (NDT) tool to characterize this Ni3 Al. For this purpose, in our technique, the two parameters such as the nearest-neighbour distance and the hardness parameter is taken as two input parameters. Ultrasonic attenuation due to the cause of e-p (electron-phonon) interaction has been evaluated from 10K to 50K, for longitudinal as well as shear waves along <100> crystallographic direction and the elastic constants (second order) for this intermetallic alloy of nickel and aluminium is also evaluated in low temperature region and the obtained results have been discussed.